A REVIEW ON HERBAL COSMETICS IN INDONESIA - Wathoni, Nasrul; Haerani, Ani; Yuniarsih, Nia; Haryanti, Retno (International Journal of Applied Pharmaceutics, 2018)
Nowadays, Herbal cosmetic is growing rapidly as most women prefer natural products rather than chemicals products for their personal care. Herbal cosmetic contains natural nutrients to improve and provide consumers satisfaction due to relatively fewer side effects compared to synthetic cosmetics. Indonesia is one of the biggest supplier's countries for herbal raw materials in cosmetic products. Many plants are available naturally as well as different uses that can be made as basic ingredients for cosmetic preparations, such as onion dayak bulb, kemuning leaf, pegagan, kecombrang, red betel, pecan, and sweet root. This review aimed to provide information on plants in Indonesia based on the phytochemicals contents that can be formulated into various categories of cosmetic preparations, such as skin care, hair care, anti-aging, skin whitening, and antioxidant.